E-health literacy of secondary school students in Saudi Arabia - Hala Alhodaib (Informatics in Medicine Unlocked, 2022)
Background: The internet has become the most important source for information access across the globe. However, it is essential that the users need a few essential skills and knowledge tips for identifying reliable sources of information, analyzing and evaluating the information, and applying the knowledge gained in real-life contexts, which is referred to as E-Health literacy. With increasing reliance on internet technologies, it is essential that school curriculums incorporate computer literacy and E-Health concepts in order to enable students to make better use of internet technologies and to prevent information misuse. Objective: The aim of this study is to investigate the E-Health literacy levels among the secondary school students in Saudi Arabia. Methods: A questionnaire-based (E-Heals) survey was adopted for collecting the data from students. Twenty-Four schools in six major cities in Saudi Arabia were selected for the study. Purposive sampling was adopted for identifying the schools, and random sampling was adopted for selecting the classes (Grade 10) in secondary schools. A total of 3134 students participated in the survey, out of which 476 incomplete surveys were identified, resulting in a final sample of 2658. Results: Medium to High E-Health literacy levels were identified among the participants. Significant differences in E-Health literacy levels was identified among male and female students (T-Value = 26.5518, p < 0.0001), and also among students in public and private schools (T-Value = 4.666, p < 0.0001). In addition, younger students exhibited a higher E-Health literacy compared to older students. Conclusions: Secondary school students reflected good E-Health literacy levels in Saudi Arabia. However, there are discrepancies in literacy levels in relation to gender and type of schools, which need to be addressed by improving more engaging pedagogic strategies for achieving good E-Health literacy rates among all students. In addition, future studies should focus on the influencing factors of E-Health literacy across various population samples.